Badanie oczekiwań kandydatów na studia wobec uczelni - Mazurek-Łopacińska, Krystyna (Research on Expectations of Studies Candidates Toward College, 2007)
A principal basis for candidates expectation's research is the identification of their criteria for choosing a college. They were presented in the first part of the article in the cross-section of basic types of studies for instance, daytime studies, part-time studies and master supplementary studies. In the second part of the article the author talks over candidates' ideas about particular features of didactic offer. A point system was used to assess these features.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 11-30